The Bible as my Witness. Issue 1 (2nd November 2021) - Parmenter, Dorina Miller
Abstract : Digital Bibles, recently available in a variety of formats on electronic devices such as phones, tablets, and e-readers, have prompted discussions among Christians about their Bible-reading preferences and analyses by scholars about the outcomes of different kinds of biblical reading practices. Rather than focusing on the semantic dimension of users' encounters with biblical texts in various media, this paper will consider how digital Bibles relate to Christians' concerns about biblical visibility, or the act of being seen reading a recognizable Bible. In some cases, digital Bibles are lauded as exceeding the benefits of the printing press to spread God's word throughout the world, for they can operate subversively and inconspicuously in circumstances where being seen with a print Bible is hazardous or undesirable. But in other contexts, Christians are encouraged to abandon their invisible digital Bibles and enact visible performances with their iconic print Bibles as an essential aspect of witnessing.